Impact of a Mock OSCE on Student Confidence in Applying the Pharmacists' Patient Care Process - Eleonso Cristobal; Kathryn Perkins; Connie Kang; Steven Chen (MDPI AG, 2024)
The Medical and Pharmacy Student Collaboration (MAPSC) student organization at the University of Southern California, Alfred E. Mann School of Pharmacy and Pharmaceutical Sciences, created an extracurricular, peer-led, virtual group mock objective structured clinical examination (MOSCE) to expose first-year pharmacy students (P1s) to the Pharmacists' Patient Care Process (PPCP). The purpose of this study is to evaluate the impact of a MAPSC MOSCE on P1s self-reported confidence in applying the PPCP and on patient communication, medication knowledge, and clinical skills. An anonymous, optional, self-reported survey was administered to P1s before and after the event, where they rated their confidence on a scale of 0-100 (0 = not confident, 100 = certainly confident). The statistical analysis was a paired two-tailed t-test with a significance level of p < 0.05. A total of 152 P1s and 30 facilitators attended the MOSCE. One hundred thirty-nine students met the inclusion criteria and were included in the data analysis. There was a statistically significant difference in the change in self-reported confidence for all PPCP components and learning outcomes. The results of our study strongly indicate that introducing P1 students to the PPCP through a MAPSC MOSCE format is a valuable experience.